Cerebral amyloid angiopathy: Review of clinico‐radiological features and mimics. Issue 4 (31st March 2018) - Sharma, Rohit; Dearaugo, Stephanie; Infeld, Bernard; O'Sullivan, Richard; Gerraty, Richard P
Summary: Cerebral amyloid angiopathy (CAA) is an important cause of lobar intracerebral haemorrhage (ICH) in the elderly, but has other clinico‐radiological manifestations. In the last two decades, certain magnetic resonance imaging (MRI) sequences, namely gradient‐recalled echo imaging and the newer and more sensitive susceptibility‐weighted imaging, have been utilised to detect susceptibility‐sensitive lesions such as cerebral microbleeds and cortical superficial siderosis. These can be utilised sensitively and specifically by the Modified Boston Criteria to make a diagnosis of CAA without the need for 'gold‐standard' histopathology from biopsy. However, recently, other promising MRI biomarkers of CAA have been described which may further increase precision of radiological diagnosis, namely chronic white matter ischaemia, cerebral microinfarcts and lobar lacunes, cortical atrophy, and increased dilated perivascular spaces in the centrum semiovale. However, the radiological manifestations of CAA, as well as their clinical correlates, may have other aetiologies and mimics. It is important for the radiologist to be aware of these clinico‐radiological features and mimics to accurately diagnose CAA. This is increasingly important in a patient demographic that has a high prevalence for use of antiplatelet and antithrombotic medications for other comorbidities which inherently carries an increased risk of ICH in patients with CAA.